Effects of heating, autoclaving and ultra-high pressure on the solubility, immunoreactivity and structure of major allergens in egg - Yan Zhang (Taylor & Francis Group, 2018)
Ovotransferrin (OVT) and ovomucoid (OVM) were treated, respectively by different food processing conditions. The protein recovery and immunoreactivity of OVT significantly decreased during heat treatment (P < .05), and aggregates appeared after dry heating at 150°C or 200°C or boiling at 100°C. OVM appeared more stable than OVT under the same treatment. Greatly reduced solubility occurred only after dry heating at 200°C. The immunoreactivity increased after dry heating at 100°C or 150°C or moist heating (60°C, boiling). Autoclave sterilization had a strong effect on the characteristics of both OVT and OVM. Ultra-high pressure had very little effect on OVT and OVM, except at 600 MPa in the moist treatment. Results showed that temperature synergistic processing with water and high pressure had the greatest impact on the characteristics, which could be a potential strategy for mitigating the negative effects of allergens in egg.